Elaboración del estudio de pre-factibilidad del montaje de una empresa de consultoría que preste servicios de asesoría en gestión de calidad a las empresas del sector hotelero para dar cumplimiento a lo expuesto en la norma técnica sectorial NTSH 006 (2016)
This document of the thesis relates the pre-feasibility study of the installation of a consulting firm that provides advisory services in quality management companies in the hotel sector, for contributing to growth and formalization of small and medium hotels Colombia, through the implementation of the Sectoral Colombian Technical Standard NTSH 006, which has as main purpose to certify in quality to establishments and aims for its possible categorization by stars. Undergraduate work, addresses the following aspects of the project: Description of the current profile of the project, identification and strategic alignment, -IAEP-, studies relating to the development, financial evaluation and essential aspects of management.